Experiências de tecnologia social e agricultura familiar: no contexto do município de Tunas do Paraná (PR) - Morges, Rafaela Novaski (2020)
This research deals with the theme on Social Technology (TS) and Sociotechnical Adequacy (AST). Related to the current discussions about the problems experienced by Family Farming, the possible experiences of Social Technology. The objective was to analyze possible experiences of Social Technology and Sociotechnical Adequacy established in the context of the Association of Rural Producers of Tunas of Paraná (APROTUNAS) mediated by the Technological Incubator of Popular Cooperatives of the Federal University of Paraná (ITCP-UFPR). The basis of the theoretical subsidy were: Technology and its relations with Society, Incubators of Popular Cooperatives and their relations with TS, and Family Agriculture and its possible intersections with Social Technology and AST. In these theoretical frameworks, the relations of how technology infers in labor relations were exposed, mainly when dealing with rural work after the modernization of the field (Green Revolution). In this sense, the research is dedicated to thinking about technological alternatives for family farming based on the analysis of the relationships between APROTUNAS and ITCP-UFPR. The research instruments used were: document analysis, focus groups and interviews, guided by the Experiences Analysis method, following the guidelines of the Project “Technologies for Social Inclusion and Public Policies in Latin America”. The analyzes were organized based on the five sets of methodology: 1) Set Description and Historical Contextualization; 2) Technological Nature and Sociotechnical Environment; 3) Economic and Environmental Sustainability Group; 4) Set of Institutional Arrangements and Links; and finally 5) Political Sustainability Group. The results sought to contribute to the theme of analysis of TS and AST experiences. Regarding the results of this research, it was possible to observe that the analyzed experience is composed of actors who are configured as family farmers in a situation of economic vulnerability, who are structured as an association seeking alternatives to market their products. These actors maintained direct relations with the Federal University of Paraná, through the ITCP-UFPR extension project. Such relationships generated income opportunities for farmers, access to public policies and also to improve environmental issues. As for the intersections between the concept of TS and the modalities of AST - use, appropriation and adjustment in the work process - in relation to experience, as well as when analyzing the proposed sets, it was found that, despite the possibilities of conformation of social technology cannot be configured as such, mainly due to the circumstance of the case in question representing several limitations of adherence, especially with regard to autonomy, self-management and the construction of technology from the pillars of Solidarity Economy and TS.